Improving the ex vivo expansion of human tumor-reactive CD8 + T cells by targeting toll-like receptors - Qiu, Chenli; Wang, Jing; Zhu, Lingyan; Cheng, Xiaobo; Xia, Bili; Jin, Yanling; Qin, Ran; Zhang, LinXia; Hu, Huiliang; Yan, Jia; Zhao, Chen; Zhang, Xiaoyan; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Toll-like receptors (TLRs) are important pattern recognition receptor(s) known to mediate the sensing of invading pathogens and subsequent immune responses. In this study, we investigate whether TLRs could be explored for the preparation of human CD8+ T cell product used in adoptive cell therapy (ACT). Following characterization of TLRs expression on human CD8+ T cells，we screened TLR-specific agonists for their ability to act in concert with anti-CD3 to stimulate the proliferation of these cells and corroborated the observed co-stimulatory effect by transcriptional profiling analyses. Consequently, we developed an optimal formulation for human CD8+ T cell amplification by combining CD3/CD28 antibody, interleukin 7 (IL-7), interleukin 15 (IL-15), and three agonists respectively targeting TLR1/2, TLR2/6, and TLR5. This new formulation performed better in amplifying PD-1+CD8+ T cells, a potential repertoire of tumor-reactive CD8+ T cells, from tumor patients than the conventional formulation. Importantly, the expanded CD8+ T cells showed a restored functionality and consequently a robust anti-tumor activity in an in vitro co-culturing system. Together, our study established the utility of TLR agonists in ex vivo expansion of tumor-targeting CD8+ T cells, thus providing a new avenue toward a more effective ACT.